2023
DOI: 10.3390/cancers15112954
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Breast Carcinoma in U.S. Population: Racial Disparities, Survival Benefit of Adjuvant Chemoradiation and Future Personalized Treatment with Genomic Landscape

Abstract: Purpose: In this population-based study, we aim to identify factors that are influential on the survival outcome in MBC and investigate novel molecular approaches in personalized disease management. Methods: The data of this study were collected from the SEER database from 2000–2018. A total of 5315 cases were extracted from the database. The data were evaluated for demographics, tumor characteristics, metastasis, and treatment. Survival analysis was completed by using SAS software for multivariate analysis, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The etiology of MpBC remains uncertain, predominantly affecting women aged over 50 years, with sporadic occurrences and minimal familial clustering ( Chaudhary et al, 2023 ). Limited data exists regarding the demographics, clinical manifestations, tumor attributes, and therapeutic approaches for MpBC, including SCC ( Ullah et al, 2023 ; Wu et al, 2023 ). The lymph node metastasis rate of MpBC was relatively low, as evidenced by a large-scale study indicating that the incidence of MpBC involving axillary lymph nodes was 21.9%, which is lower than that of invasive ductal carcinoma (IDC) at 34.3% ( Pezzi et al, 2007 ; Lee et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of MpBC remains uncertain, predominantly affecting women aged over 50 years, with sporadic occurrences and minimal familial clustering ( Chaudhary et al, 2023 ). Limited data exists regarding the demographics, clinical manifestations, tumor attributes, and therapeutic approaches for MpBC, including SCC ( Ullah et al, 2023 ; Wu et al, 2023 ). The lymph node metastasis rate of MpBC was relatively low, as evidenced by a large-scale study indicating that the incidence of MpBC involving axillary lymph nodes was 21.9%, which is lower than that of invasive ductal carcinoma (IDC) at 34.3% ( Pezzi et al, 2007 ; Lee et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, it can be concluded that there are different points of view about the effect of using NAC or adjuvant chemotherapy on patients’ survival rates. In one of the most extensive studies conducted recently by Ullah et al 13 the results show that the simultaneous use of surgery, radiotherapy, and chemotherapy, compared to the use of each of them alone or the combination of two methods, can increase patients’ survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 According to the study by Ullah et al age of more than 60 years, grade IV tumors, tumor size more than 50 mm, and brain metastasis could affect patients' survival rate and increase patients' mortality rate. 13 Breast carcinosarcoma usually shaped solid, well-defined, nodular, and firm tumors. 14 It is a malignant tumor, especially a large tumor, which could lead to skin and/or chest wall fixation, nipple retraction, skin redness, erythema, and ulceration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation